Empowering Ageing: Navigating the Future of Digital Healthcare for Older Adults – a Rapid Reviewof Perspectives and Challenges - Andrea Tales (KEEP ON PLANNING FOR THE REAL WORLD. Climate Change calls for Nature-based Solutions and Smart Technologies, 2024)
Digital health offers innovative and promising solutions addressing the challenges of an ageing population.The pandemic has shown the advantages of treating and monitoring patients with assisted technology andtheir cost-effectiveness. Several studies demonstrate that older people can benefit from assisted technologyto monitor their health, manage their medication and treatment, and receive online consultations byhealthcare providers. Nevertheless, a growing literature show conflicting results with respect to theintegration of digital devices for older people in practice. Integration of digital health means to explore howdifferent processes are employed, incorporated and connected with each other in order to realise a positiveoutcome for older people. Recent studies demonstrate that older people use the internet in diverse ways anda gender gap has been noticed in the way older men and older women make use of modern technology ineveryday life. Moreover, some studies suggest that Ageism would pose a risk of excluding older people touse digital health. However, some focus on older people’s experiences and perceptions which determine theuse of digital technology and the meaning for them. Hence, there is a sparse understanding of how digitalhealth is implemented and experienced by older people in practice. Therefore, this paper provides a rapidreview of the gaps of knowledge and understanding in how digital health is implemented, perceived, andexperienced by older people.The objectives are: 1. To examine the practical applications and effectiveness of assisted technology in thecare of older adults, specifically focusing on health outcomes. 2. To descriptively map the key themes andtrends in assisted technology for older adults, aiding in the formulation of targeted future research priorities.By addressing these objectives, this paper aspires to contribute to the advancement of digital health for olderadults, offering insights that can inform policy, practice, and future research endeavours.